Identifying contributing variables on rice production: Case study of rural smallholder farmers - Berlian, Gladys; Setiawan, Budi; Wahyuningtyas, Agustina Shinta Hartati (Anjoro: International Journal of Agriculture and Business, 2024)
Risks faced by agricultural actors in the food commodity sector can affect farmers' ability to meet food supply needs. Decreased production in rice commodities is one phenomenon that often occurs. The decline in production can be caused by various factors. The purpose of this study is to determine the effect of land area, number of seeds, land fragmentation, and the extent of pest attacks on production yields and to determine the level of criticality of each risk faced by agricultural actors that affect production decline. This study uses Multiple Linear Regression analysis to determine the production factors that affect production yields and Failure Mode Effect Analysis (FMEA) is used to determine the level of criticality of the risks faced. The results of this study state that the variables of land area, seeds, and land fragmentation have a positive relationship to production yields while the variable area of pest attack has a negative relationship to production yields. In the FMEA analysis, it is known that the level of criticality of each risk faced by agricultural actors is the risk of supply to suppliers, production risk to farmers, social risk to farmer groups, and institutional risk to extension workers.